Estudo comparativo de desempenho entre acumuladores íon-lítio e chumbo-ácido para uso na energia solar residencial off-grid - Alencar, Rayssa Ferreira (2022)
Clean and renewable energies have been increasingly important for the progress of decentralized development. In Brazil, self-generated power has placed residential consumers at the center of photovoltaic expansion and, for that, the number of studies involving accumulators for the generation of this type of energy is growing. Lead-acid and lithium-ion batteries are widely used devices for energy storage, such as electricity generation in off-grid residential autonomous photovoltaic systems. This research has presented the development of a prototype system proper for the performance analysis of two types of battery banks, one of lead-acid (LA) and another of lithium-ion (LI), by measuring voltage drop data when the batteries are discharged. LA batteries of 14 A and LI batteries of 10.4 A were used and the proportionality between them was applied. After the tests, measurements and data analysis it was noticed that, in the studied range, the voltage drops in the two batteries were linear. With the results and including the technical (capacity, reliability) and commercial (price, availability) issues and the conditions applied, the lead-acid battery is the most recommended to be used in systems involving accumulators for off-grid energy generation.